Real time thermal photon-photon interactions in the mixed space - Ahmed, M. A. A.; Zainuddin, H.; Shah, N. M.; Ladrem, Madjid Lakhdar Hamou (World Scientific, 2022)
Using the effective Lagrangian for the low energy/temperature of photon–photon interaction and the lowest-order photon self-energy is calculated in the Real-Time Formalism (RTF) for an arbitrary path specified by the σ-parameter within the new basis. The causal Green’s functions (without chemical potential) for the scalar field are evaluated to derive the usual thermal propagators in the mixed space. It is shown that the symmetric propagator does not depend on σ-parameter. Furthermore, the photon self-energy is used to calculate some electromagnetic properties, such as dielectric tensor and velocity of light from photon self-energy in the mixed space that greatly simplifies calculations in RTF. Their time dependence is investigated, and a comparison between our results and those obtained by other models is discussed.